PENGEMBANGAN KECERDASAN SPIRITUAL PESERTA DIDIK DI SDIT WIHDATUL UMMAH MAKASSAR - Sakina; Muljono Damopolii; Ahmad Afif (JIPMI (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah), 2022)
The main problem in this study is the development of students' spiritual intelligence in SDITWihdatul Ummah Makassar. This study aims: 1) to know the methods of developing spiritualintelligence of students, 2) to know the implementation of developing spiritual intelligence inextracurricular activities of students, 3) to know the various supporting and inhibiting factors fordeveloping spiritual intelligence of students and the solution, 4) find out the results of developing thespiritual intelligence of students. This research is a qualitative research conducted in the form of a casestudy. The research location is SDIT Wihdatul Ummah Makassar. Furthermore, the data collectionmethods used are observation, interview, documentation and reference tracking. Furthermore, dataprocessing and analysis techniques are carried out by means of data reduction, data presentation, andconclusion drawing. The results of this study indicate that: 1) The method of developing spiritualintelligence is applied by teachers in SDIT Wihdatul Ummah Makassar, namely the lecture method,the method of spiritual stories, the method of involving students in religious rituals, the method ofgiving assignments and the question and answer method. 2) Implementation of the development of spiritual intelligence of students in extracurricular activities at SDIT Wihdatul Makassar, namelytarbiyat al-aula>d, tah}fi>z} al-Qur'a>n, MABIT (Night to build faith and piety), and scouts . 3)Factors supporting the development of students' spiritual intelligence in SDIT Wihdatul UmmahMakassar are teacher's abilities and teacher's knowledge. While the inhibiting factors are theenvironment, different educational patterns and lack of response from parents of students. 4) Theresults of the development of spiritual intelligence are able to have a positive impact on students suchas the understanding of the faith they have gotten from the start, , creating a rabbani attitude towardsstudents, fostering a level of self-awareness , fostering a sense of caring among others, able to foster thecreativity of participants in the effort to develop their own potential, and able to comply with theregulations in school.